Paper No 19.3: Back‐Channel‐Etch Process Flow for a‐IGZO TFTs. (September 2013) - Nag, Manoj; Steudel, Soeren; Chasin, Adrian; Myny, Kris; Rockele, Maarten; Bhoolokam, Ajay; Willegems, Myriam; Smout, Steve; Vicca, Peter; Ameys, Marc; Schols, Sarah; Cheyns, David; et al.
Abstract: In this study, the authors report high‐quality amorphous Indium‐Gallium‐Zinc‐Oxide (a‐IGZO) thin film transistors (TFTs) fabricated using a new back‐channel‐etch (BCE) process flow on Polyethylene Naphthalate (PEN) foil. The BCE flow allows a better scalability of TFTs for high‐resolution backplanes and related circuits. The maximum processing temperature was limited to less than 165 o C in order to ensure good overlay accuracy (< 1µm) on foil. The presented process flow differs from to previously reported by defining the Mo S/D contacts by dry etch prior to a‐IGZO patterning. The TFTs show good electrical performance, including field‐effect mobilities in the range of 15.0cm 2 /(V.s), sub‐threshold slopes of 0.3V/decade and off‐currents <1.0pA on foil. Finally, the applicability of this new BCE process flow was demonstrated for TFT backplane driving a 32 x 32 active‐matrix organic light‐emitting diode (AMOLED) display.